Experimental Study on the Surface Properties of Nanoalumina-Filled Epoxy Resin Nanocomposites - Pinto, Deesy (2020)
This article presents an experimental study on the surface properties of epoxy resin nanocomposites (EPNCs) manufactured with a thermosetting epoxy resin (EP)–bisphenolAdiglycidyl ether (BADGE)–2-[[4-[2-[4-(Oxiran-2-ylmethoxy)phenyl]propan-2-yl]phenoxy]methyl]oxirane) and filled with alumina nanoparticles (NPs). The NPs consist of pretreated (with a silane agent) alpha alumina with irregular shapes and a 100nmmaximumsize. Three weight fractions of NPs were studied: 1, 3, and 5 wt. (%). Two di erent epoxy (EP) resins were manufactured, one cured and postcured with bis (4-aminophenyl) methane (DDM); and another one cured with 3-dodec-2-enyloxolane-2,5-dione (DDSA) + 8-methyl-3a,4,7,7a-tetrahydro-4,7-methano-2-benzofuran-1,3-dione (MNA). The wettability and the surface roughness of the obtained EPNCs were studied through the measurement of contact angles and topographic images obtained with atomic force microscopy (AFM), respectively. Significant influence of both the loading of NPs and used curing agents was observed. EPNCs cured with DDM were shown to be hydrophobic for 0, 1, and 3 wt. (%) and hydrophilic for 5 wt. (%). Maximum surface roughness was observed for 5 wt. (%). EPNCs cured with DDSA+MNA were shown to be hydrophilic for 0 and 1 wt. (%) and hydrophobic for 3 and 5 wt. (%). The surface roughness decreased as the weight fraction of NPs increased until 3 wt. (%), and then increased for 5 wt. (%).